AN EVALUATION OF TECHNICAL REPORT WRITING SYLLABUS AT THE PREPARATORY YEAR PROGRAM - Soada Idris Khan (English Review: Journal of English Education, 2018)
The current study aims to critically analyze the contents of the Technical Report Writing syllabus as well as identify whether the syllabus meets course objectives or not. The study also suggests some remedies to improve the contents of the syllabus. As part of the study, twenty EFL teachers from Preparatory Year Program were selected for this study. A quantitative questionnaire containing 10 statements was administered to gather data from the participants. In addition, an interview session with a set of 5 questions based on the key elements on the current syllabus was also conducted with the teachers to have their expert opinion and suggestions. The analysis of data revealed that textbook is appropriate for the students and needs not be replaced. However, syllabus should include some more activities that may address to the needs of weak students. The study also suggests teachers to exploit other resources (from internet or library) in order to give an extra push to the learners.Keywords: course objectives; syllabus analysis; technical report writing.